A quick-repair expansion joint polyurethane elastomer composition and preparation method thereof
By preparing straw cellulose-polyurethane-graphene composite material and introducing 4,4'-dicarboxydiphenyldisulfide, the problems of poor heat dissipation effect, easy aging and poor mechanical properties of the polyurethane material are solved, and the mechanical properties of the material are improved, the thermal conductivity enhancement and self-repair ability of the material are improved.
Patent Information
- Application Number
- CN202411545732.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing polyurethane materials have poor heat dissipation effect, are prone to aging, and have poor mechanical properties.
By preparing straw cellulose-polyurethane-graphene composite material, 4,4'-dicarboxydiphenyldisulfide is introduced to improve the mechanical properties and thermal conductivity of the material and achieve self-healing effect.
It improves the mechanical properties and thermal conductivity of the material, extends the service life, and improves the self-healing ability.
Smart Images

Figure CN119081441B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane elastomers, and specifically refers to a quick-repair expansion joint polyurethane elastomer composition and a preparation method thereof. Background Art
[0002] As the transition section in the bridge structure, the expansion joint of the bridge is the weak link in the overall structure of the bridge. Cracks often appear in the early stage of the bridge's service life, thus destroying the stress characteristics of the overall structure of the bridge and greatly reducing the service life of the bridge. With the continuous improvement of my country's economic level, traffic flow has become increasingly complex, a large number of high-grade highways and super-large highway bridges have been built one after another, and the types of bridges have gradually developed towards large lengths, which requires bridge expansion devices to meet the needs of large displacements while ensuring reasonable structures. According to the material characteristics of expansion joints, the more commonly used polymer elastomer expansion joints are mainly divided into three categories: rubber combination, modified asphalt material and polyurethane elastomer. Among them, polyurethane elastomer expansion joints are bridge elastomer expansion joints composed entirely of polymer materials, mainly using polyurethane as a polymer caulking material. This type of bridge joint material has been successfully applied in engineering practice. It has the advantages of easy construction and maintenance, good strength, elasticity and ductility, but poor heat and water resistance, large internal heat rise, and easy aging.
[0003] The existing technology currently has the following main problems: polyurethane has poor heat dissipation effect, is easy to age, and has poor mechanical properties. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a quick-repair expansion joint polyurethane elastomer composition and a preparation method thereof. In order to solve the problems of poor heat dissipation effect, easy aging and poor mechanical properties of polyurethane materials, the present invention proposes to prepare a straw cellulose-polyurethane-graphene composite material to improve the mechanical properties and thermal conductivity of the material, and introduce 4,4'-dicarboxy diphenyl disulfide to achieve an improvement in the self-repair effect of the material, thereby achieving the technical effect of increasing the service life of the material.
[0005] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: The present invention proposes a quick-repair expansion joint polyurethane elastomer composition and a preparation method thereof, wherein the quick-repair expansion joint polyurethane elastomer composition is prepared from the following components in parts by weight: 53-62 parts of corn stalks, 32-46 parts of diphenylmethane-4,4'-diisocyanate, 7-10 parts of polytetrahydrofuran, 0.5-0.6 parts of pentamethyldiethylenetriamine, 6-9 parts of polyethylene glycol, 1.6-2.2 parts of 4,4'-dicarboxy diphenyl disulfide, 3.5-5 parts of 1,4-butanediol and 0.9-1.6 parts of modified graphene.
[0006] Preferably, the method for preparing the modified graphene specifically comprises the following steps:
[0007] (1) adding graphene oxide in an amount of 0.8-1.2 mg / mL to anhydrous N,N-dimethylformamide, magnetically stirring at a speed of 500-700 rpm for 2 h, and ultrasonically dispersing at a power of 180-200 W for 1 h to obtain a graphene oxide dispersion;
[0008] (2) adding hexamethylene diisocyanate and dibutyltin dilaurate in amounts of 100-120 mg / mL and 0.15-0.25 mg / mL, respectively, to the graphene oxide dispersion obtained in step (1) to obtain a mixed dispersion;
[0009] (3) The mixed dispersion obtained in step (2) was transferred to a reactor, nitrogen was introduced to exclude air, the mixture was stirred at 80° C. for 4 h, and the mixture was washed three times with anhydrous N,N-dimethylformamide and dried to obtain modified graphene.
[0010] Preferably, the method for preparing the quick-repair expansion joint polyurethane elastomer composition specifically comprises the following steps:
[0011] S1. Wash, dry and crush corn stalks through an 80-mesh sieve to obtain stalk powder. Add the stalk powder to a 5% NaOH solution at a concentration of 0.05 g / mL, stir in a water bath, and filter to obtain modified stalk powder.
[0012] S2, adding the modified straw powder obtained in S1 to a sodium chlorite solution with a molar concentration of 0.25 mol / L at an addition amount of 0.1 g / mL, adjusting the pH to 6.5, stirring in a water bath, filtering and washing to obtain straw cellulose;
[0013] S3, adding diphenylmethane-4,4'-diisocyanate and polytetrahydrofuran into a reactor, filling with nitrogen to exclude oxygen, stirring at 300 rpm in a water bath at 80°C for 35 min, adding pentamethyldiethylenetriamine, stirring at 80 rpm in a water bath at 80°C for 140 min, to obtain a polymer;
[0014] S4, adding the modified graphene to anhydrous N,N-dimethylformamide, ultrasonically dispersing to prepare a dispersion liquid with a mass fraction of 3%, adding polyethylene glycol, introducing nitrogen to exclude oxygen, and magnetically stirring to keep the mixture at 80°C to obtain a mixed solution;
[0015] S5, adding the oligomer mixed solution obtained in S3 to the mixed solution obtained in S4, adding 1,4-butanediol and 4,4'-dicarboxyl diphenyl disulfide, stirring in a water bath, and drying to obtain an isocyanate-terminated polyurethane;
[0016] S6. Add the terminal isocyanate polyurethane obtained in S5 into anhydrous N,N-dimethylacetamide in an amount of 0.4 g / mL, add the straw cellulose obtained in S2, stir in a water bath, and obtain a quick-repair expansion joint polyurethane elastomer composition.
[0017] Preferably, in S1, the water bath stirring temperature is 60-70°C, the stirring speed is 120-160rpm, and the stirring time is 15-20min;
[0018] Preferably, in S2, the water bath stirring temperature is 70-80°C, the stirring speed is 130-150rpm, and the stirring time is 25-40min;
[0019] Preferably, in S4, the magnetic stirring speed is 250-350 rpm, and the stirring time is 50-60 min;
[0020] Preferably, in S5, the water bath stirring temperature is 76-89°C, the stirring speed is 80-120 rpm, and the stirring time is 6-15 min;
[0021] Preferably, in S6, the water bath stirring temperature is 72-86°C, the stirring speed is 700-900 rpm, and the stirring time is 80-90 min.
[0022] The beneficial effects achieved by the present invention are as follows: graphene oxide is modified with hexamethylene diisocyanate, and a large number of oxygen-containing groups, such as hydroxyl groups, carboxyl groups and epoxy groups, exist on the surface of graphene oxide. The isocyanate groups are used to react with the oxygen-containing functional groups of graphene oxide to graft hexamethylene diisocyanate onto the graphene oxide, which not only improves the dispersibility of graphene oxide in the solution, but also reacts with the hydroxyl groups in the soft segment structure to make it uniformly dispersed in the polyurethane, thereby improving the loading rate of graphene oxide and the stability of the material; graphene has very excellent mechanical properties, high specific surface area and diisocyanate. The two-dimensional structure of graphene oxide increases the interface strength and compatibility of the material. The two-dimensional structure of graphene oxide can prevent the expansion of cracks in the material during stretching, thereby improving the elasticity and strength of the material. Graphene has a high thermal conductivity, which is beneficial to the transmission and release of heat. The evenly dispersed graphene can improve the overall thermal conductivity of the material and reduce the heat accumulation inside the material. Compared with single-component polyurethane, cellulose composite polyurethane is used as the matrix. The formation of a fine pore structure is conducive to liquid discharge. At the same time, the introduction of disulfide bonds through 4,4'-dicarboxy diphenyl disulfide improves the self-healing ability of polyurethane. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a result diagram of the heat dissipation performance test of Examples 1-3 and Comparative Examples 1-2.
[0024] Figure 2It is the result diagram of tensile strength of Example 1-3 and Comparative Example 1-2.
[0025] Figure 3 It is the result diagram of the elongation at break of Example 1-3 and Comparative Example 1-2.
[0026] Figure 4 It is a result diagram of the repair performance test of Examples 1-3 and Comparative Example 3.
[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0031] Example 1
[0032] A quick-repair expansion joint polyurethane elastomer composition is prepared from the following components in parts by weight: 62 parts of corn stalks, 46 parts of diphenylmethane-4,4'-diisocyanate, 10 parts of polytetrahydrofuran, 0.6 parts of pentamethyldiethylenetriamine, 9 parts of polyethylene glycol, 2.2 parts of 4,4'-dicarboxy diphenyl disulfide, 5 parts of 1,4-butanediol and 1.6 parts of modified graphene.
[0033] The preparation method of modified graphene specifically comprises the following steps:
[0034] (1) adding graphene oxide at an addition amount of 1.2 mg / mL to anhydrous N,N-dimethylformamide, magnetically stirring at a speed of 700 rpm for 2 h, and ultrasonically dispersing at a power of 200 W for 1 h to obtain a graphene oxide dispersion;
[0035] (2) adding hexamethylene diisocyanate and dibutyltin dilaurate in amounts of 120 mg / mL and 0.25 mg / mL, respectively, to the graphene oxide dispersion obtained in step (1) to obtain a mixed dispersion;
[0036] (3) The mixed dispersion obtained in step (2) was transferred to a reactor, nitrogen was introduced to exclude air, the mixture was stirred at 80° C. for 4 h, and the mixture was washed three times with anhydrous N,N-dimethylformamide and dried to obtain modified graphene.
[0037] The preparation method of the quick-repair expansion joint polyurethane elastomer composition specifically comprises the following steps:
[0038] S1. Wash, dry and crush corn stalks through an 80-mesh sieve to obtain stalk powder. Add 0.05 g / mL of the stalk powder to a 5% NaOH solution, stir at 160 rpm in a 70°C water bath for 20 min, and filter to obtain modified stalk powder.
[0039] S2, adding the modified straw powder obtained in S1 to a sodium chlorite solution with a molar concentration of 0.25 mol / L at an addition amount of 0.1 g / mL, adjusting the pH to 6.5, stirring at 150 rpm in a water bath at 80°C for 40 min, filtering and washing to obtain straw cellulose;
[0040] S3, adding diphenylmethane-4,4'-diisocyanate and polytetrahydrofuran into a reactor, filling with nitrogen to exclude oxygen, stirring at 300 rpm in a water bath at 80°C for 35 min, adding pentamethyldiethylenetriamine, stirring at 80 rpm in a water bath at 80°C for 140 min, to obtain a polymer;
[0041] S4, adding the modified graphene to anhydrous N,N-dimethylformamide, ultrasonically dispersing to prepare a dispersion with a mass fraction of 3%, adding polyethylene glycol, introducing nitrogen to exclude oxygen, and reacting at 80°C with magnetic stirring at 350 rpm for 60 minutes to obtain a mixed solution;
[0042] S5, adding the oligomer mixed solution obtained in S3 to the mixed solution obtained in S4, adding 1,4-butanediol and 4,4'-dicarboxyl diphenyl disulfide, stirring at 120 rpm in a water bath at 89°C for 15 min, and drying to obtain an isocyanate-terminated polyurethane;
[0043] S6. Add the terminal isocyanate polyurethane obtained in S5 to anhydrous N,N-dimethylacetamide in an amount of 0.4 g / mL, add the straw cellulose obtained in S2, stir at 900 rpm in a water bath at 86°C for 90 minutes, and obtain a quick-repair expansion joint polyurethane elastomer composition.
[0044] Example 2
[0045] A quick-repair expansion joint polyurethane elastomer composition is prepared from the following components in parts by weight: 53 parts of corn stalks, 32 parts of diphenylmethane-4,4'-diisocyanate, 7 parts of polytetrahydrofuran, 0.5 parts of pentamethyldiethylenetriamine, 6 parts of polyethylene glycol, 1.6 parts of 4,4'-dicarboxy diphenyl disulfide, 3.5 parts of 1,4-butanediol and 0.9 parts of modified graphene.
[0046] The preparation method of modified graphene specifically comprises the following steps:
[0047] (1) adding graphene oxide at an amount of 0.8 mg / mL to anhydrous N,N-dimethylformamide, stirring magnetically at a speed of 500 rpm for 2 h, and ultrasonically dispersing at a power of 180 W for 1 h to obtain a graphene oxide dispersion;
[0048] (2) adding hexamethylene diisocyanate and dibutyltin dilaurate in amounts of 100 mg / mL and 0.15 mg / mL, respectively, to the graphene oxide dispersion obtained in step (1) to obtain a mixed dispersion;
[0049] (3) The mixed dispersion obtained in step (2) was transferred to a reactor, nitrogen was introduced to exclude air, the mixture was stirred at 80° C. for 4 h, and the mixture was washed three times with anhydrous N,N-dimethylformamide and dried to obtain modified graphene.
[0050] The preparation method of the quick-repair expansion joint polyurethane elastomer composition specifically comprises the following steps:
[0051] S1. Wash, dry and crush corn stalks through an 80-mesh sieve to obtain stalk powder. Add 0.05 g / mL of the stalk powder to a 5% NaOH solution, stir at 120 rpm in a 60°C water bath for 15 min, and filter to obtain modified stalk powder.
[0052] S2, adding the modified straw powder obtained in S1 to a sodium chlorite solution with a molar concentration of 0.25 mol / L at an addition amount of 0.1 g / mL, adjusting the pH to 6.5, stirring at 130 rpm in a 70°C water bath for 25 min, filtering and washing to obtain straw cellulose;
[0053] S3, adding diphenylmethane-4,4'-diisocyanate and polytetrahydrofuran into a reactor, filling with nitrogen to exclude oxygen, stirring at 300 rpm in a water bath at 80°C for 35 min, adding pentamethyldiethylenetriamine, stirring at 80 rpm in a water bath at 80°C for 140 min, to obtain a polymer;
[0054] S4, adding the modified graphene to anhydrous N,N-dimethylformamide, ultrasonically dispersing to prepare a dispersion with a mass fraction of 3%, adding polyethylene glycol, introducing nitrogen to exclude oxygen, and reacting at 80°C with magnetic stirring at 250 rpm for 50 minutes to obtain a mixed solution;
[0055] S5, adding the oligomer mixed solution obtained in S3 to the mixed solution obtained in S4, adding 1,4-butanediol and 4,4'-dicarboxy diphenyl disulfide, stirring at 80 rpm for 6 min in a 76°C water bath, and drying to obtain an isocyanate-terminated polyurethane;
[0056] S6. Add the terminal isocyanate polyurethane obtained in S5 to anhydrous N,N-dimethylacetamide in an amount of 0.4 g / mL, add the straw cellulose obtained in S2, stir at 700 rpm in a 72°C water bath for 80 min, and obtain a quick-repair expansion joint polyurethane elastomer composition.
[0057] Example 3
[0058] A quick-repair expansion joint polyurethane elastomer composition is prepared from the following components in parts by weight: 57.5 parts of corn stalks, 39 parts of diphenylmethane-4,4'-diisocyanate, 8.5 parts of polytetrahydrofuran, 0.55 parts of pentamethyldiethylenetriamine, 7.5 parts of polyethylene glycol, 1.9 parts of 4,4'-dicarboxyl diphenyl disulfide, 4.25 parts of 1,4-butanediol and 1.25 parts of modified graphene.
[0059] The preparation method of modified graphene specifically comprises the following steps:
[0060] (1) adding graphene oxide at an amount of 1 mg / mL to anhydrous N,N-dimethylformamide, magnetically stirring at a speed of 600 rpm for 2 h, and ultrasonically dispersing at a power of 190 W for 1 h to obtain a graphene oxide dispersion;
[0061] (2) adding hexamethylene diisocyanate and dibutyltin dilaurate in amounts of 110 mg / mL and 0.2 mg / mL, respectively, to the graphene oxide dispersion obtained in step (1) to obtain a mixed dispersion;
[0062] (3) The mixed dispersion obtained in step (2) was transferred to a reactor, nitrogen was introduced to exclude air, the mixture was stirred at 80° C. for 4 h, and the mixture was washed three times with anhydrous N,N-dimethylformamide and dried to obtain modified graphene.
[0063] The preparation method of the quick-repair expansion joint polyurethane elastomer composition specifically comprises the following steps:
[0064] S1. Wash, dry and crush corn stalks through an 80-mesh sieve to obtain stalk powder. Add 0.05 g / mL of the stalk powder to a 5% NaOH solution, stir at 140 rpm in a 65°C water bath for 17.5 min, and filter to obtain modified stalk powder.
[0065] S2, adding the modified straw powder obtained in S1 to a sodium chlorite solution with a molar concentration of 0.25 mol / L at an addition amount of 0.1 g / mL, adjusting the pH to 6.5, stirring at 140 rpm in a 75°C water bath for 32.5 min, filtering and washing to obtain straw cellulose;
[0066] S3, adding diphenylmethane-4,4'-diisocyanate and polytetrahydrofuran into a reactor, filling with nitrogen to exclude oxygen, stirring at 300 rpm in a water bath at 80°C for 35 min, adding pentamethyldiethylenetriamine, stirring at 80 rpm in a water bath at 80°C for 140 min, to obtain a polymer;
[0067] S4, adding the modified graphene to anhydrous N,N-dimethylformamide, ultrasonically dispersing to prepare a dispersion with a mass fraction of 3%, adding polyethylene glycol, introducing nitrogen to exclude oxygen, and reacting at 80°C with magnetic stirring at 300 rpm for 55 minutes to obtain a mixed solution;
[0068] S5, adding the oligomer mixed solution obtained in S3 to the mixed solution obtained in S4, adding 1,4-butanediol and 4,4'-dicarboxy diphenyl disulfide, stirring in a water bath at 83°C at 100 rpm for 10.5 min, and drying to obtain an isocyanate-terminated polyurethane;
[0069] S6. Add the terminal isocyanate polyurethane obtained in S5 to anhydrous N,N-dimethylacetamide in an amount of 0.4 g / mL, add the straw cellulose obtained in S2, stir at 800 rpm in a 79°C water bath for 85 min, and obtain a quick-repair expansion joint polyurethane elastomer composition.
[0070] Comparative Example 1
[0071] This comparative example provides a polyurethane elastomer composition, which differs from Example 1 only in that graphene oxide is used to replace modified graphene in the components, and the other components and component contents are the same as those in Example 1.
[0072] Comparative Example 2
[0073] This comparative example provides a polyurethane elastomer composition, which differs from Example 1 only in that the components do not contain graphene oxide, and the other components and component contents are the same as those in Example 1.
[0074] Comparative Example 3
[0075] This comparative example provides a polyurethane elastomer composition, which differs from Example 1 only in that the composition does not contain 4,4'-dicarboxy diphenyl disulfide, and the remaining components and component contents are the same as those in Example 1.
[0076] 1. Heat dissipation performance test
[0077] Examples 1-3 and Comparative Examples 1-2 with a length of 15 cm and a length and width of 0.5 mm were placed on a 100° C. heating table for a heat dissipation performance test. The polyurethane surface temperature on the heating table was measured and recorded at a vertical distance of 20 cm using an infrared thermal imager.
[0078] Figure 1 It is a result graph of the heat dissipation performance test of Examples 1-3 and Comparative Examples 1-2. As shown in the figure, the surface temperatures of Examples 1-3 are 76.5°C, 76.9°C, and 77.0°C, respectively, and the temperatures of Comparative Examples 1-2 are 65.1°C and 40.9°C, respectively; the surface temperatures of Examples 1-3 are significantly higher than those of Comparative Example 1, indicating that the use of modified graphene improves the heat dissipation performance of the material, and the surface temperatures of Examples 1-3 are significantly higher than those of Comparative Example 2, indicating that the use of graphene oxide improves the heat dissipation performance of the material; graphene has a high thermal conductivity, which is beneficial to the transmission and release of heat, and hexamethylene diisocyanate modifies graphene, so that isocyanate is loaded on graphene, and finally the graphene is evenly dispersed and combined with the polyurethane material, thereby increasing the load rate and dispersion effect, and improving the heat dissipation performance of the material.
[0079] 2. Mechanical properties test
[0080] The tensile properties of Examples 1-3 and Comparative Examples 1-2 were tested using a single-filament strength meter to evaluate their mechanical properties. Ten samples of each type were taken, the tensile speed was 10 mm / min, the gauge length was 10 mm, the tensile strength and elongation at break were recorded each time, and the average was taken as the tensile strength and elongation at break of the sample.
[0081] Figure 2 The result diagram of the tensile strength of Examples 1-3 and Comparative Examples 1-2 is shown in the figure. As shown in the figure, the tensile strengths of Examples 1-3 are 35.6 MPa, 35.1 MPa, and 35.9 MPa, respectively, and the tensile strengths of Comparative Examples 1-2 are 29.6 MPa and 16.3 MPa, respectively; the tensile strengths of Examples 1-3 are significantly higher than that of Comparative Example 1, indicating that the use of modified graphene improves the tensile strength of the material, and the tensile strengths of Examples 1-3 are significantly higher than that of Comparative Example 2, indicating that the use of graphene oxide improves the tensile strength of the material;
[0082] Figure 3It is a result graph of the elongation at break of Examples 1-3 and Comparative Example 1-2. As shown in the figure, the elongations at break of Examples 1-3 are 613.4%, 626.1% and 613.2%, respectively, and the elongations at break of Comparative Example 1-2 are 532.9% and 435.6%, respectively; the elongations at break of Examples 1-3 are significantly higher than that of Comparative Example 1, indicating that the use of modified graphene improves the elongation at break of the material, and the elongations at break of Examples 1-3 are significantly higher than that of Comparative Example 2, indicating that the use of graphene oxide improves the elongation at break of the material; hexamethylene diisocyanate makes graphene evenly dispersed and combined with fibers, and graphene has very excellent mechanical properties, high specific surface area and two-dimensional structure. The high specific surface area is conducive to the interaction with the matrix to increase the interface strength and compatibility of the material, and the two-dimensional structure can prevent the expansion of cracks in the material during the stretching process, thereby improving the strength and toughness of the material.
[0083] 3. Repair performance test
[0084] The polyurethanes of Examples 1-3 and Comparative Example 3 were cut into dumbbell-shaped strips using a cutter, and the repair performance was tested using a single-column universal material testing machine from the German ZWICK company. The tensile rate was set to 100 mm / min, and all samples were tested more than 3 times to take the average value. After the polyurethane strips were cut with a blade, a drop of acetic acid was added and the temperature was raised for 24 hours before the tensile test. The repair efficiency of the polyurethane was calculated as follows:
[0085] Repair rate = tensile strength after repair / initial tensile strength × 100%.
[0086] Figure 4 This is a graph showing the results of the repair performance test of Examples 1-3 and Comparative Example 3. As shown in the figure, the repair rates of Examples 1-3 and Comparative Example 3 are 83.6%, 83.3%, 82.9% and 63.2%, respectively. The repair rate of Examples 1-3 is significantly greater than that of Comparative Example 3, indicating that the use of 4,4'-dicarboxy diphenyl disulfide improves the self-healing ability of the material.
[0087] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0088] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A quick-repair expansion joint polyurethane elastomer composition, characterized in that: The modified graphene is prepared from the following components in parts by weight: 53-62 parts of corn stalks, 32-46 parts of diphenylmethane-4,4'-diisocyanate, 7-10 parts of polytetrahydrofuran, 0.5-0.6 parts of pentamethyldiethylenetriamine, 6-9 parts of polyethylene glycol, 1.6-2.2 parts of 4,4'-dicarboxyl diphenyl disulfide, 3.5-5 parts of 1,4-butanediol and 0.9-1.6 parts of modified graphene; the preparation method of the modified graphene specifically comprises the following steps: (1) adding graphene oxide in an amount of 0.8-1.2 mg / mL to anhydrous N,N-dimethylformamide, magnetically stirring at a speed of 500-700 rpm for 2 h, and ultrasonically dispersing at a power of 180-200 W for 1 h to obtain a graphene oxide dispersion; (2) adding hexamethylene diisocyanate and dibutyltin dilaurate in amounts of 100-120 mg / mL and 0.15-0.25 mg / mL, respectively, to the graphene oxide dispersion obtained in step (1) to obtain a mixed dispersion; (3) transferring the mixed dispersion obtained in step (2) into a reactor, introducing nitrogen to exclude air, stirring and reacting at 80° C. for 4 h, washing with anhydrous N,N-dimethylformamide for 3 times, and drying to obtain modified graphene; The preparation method of the quick-repair expansion joint polyurethane elastomer composition specifically comprises the following steps: S1. Wash, dry and crush corn stalks through an 80-mesh sieve to obtain stalk powder. Add the stalk powder to a 5% NaOH solution at a concentration of 0.05 g / mL, stir in a water bath, and filter to obtain modified stalk powder. S2, adding the modified straw powder obtained in S1 to a sodium chlorite solution with a molar concentration of 0.25 mol / L at an addition amount of 0.1 g / mL, adjusting the pH to 6.5, stirring in a water bath, filtering and washing to obtain straw cellulose; S3, adding diphenylmethane-4,4'-diisocyanate and polytetrahydrofuran into a reactor, filling with nitrogen to exclude oxygen, stirring at 300 rpm in a water bath at 80°C for 35 min, adding pentamethyldiethylenetriamine, stirring at 80 rpm in a water bath at 80°C for 140 min, to obtain a polymer; S4, adding the modified graphene to anhydrous N,N-dimethylformamide, ultrasonically dispersing to prepare a dispersion liquid with a mass fraction of 3%, adding polyethylene glycol, introducing nitrogen to exclude oxygen, and magnetically stirring to keep the mixture at 80°C to obtain a mixed solution; S5, adding the oligomer mixed solution obtained in S3 to the mixed solution obtained in S4, adding 1,4-butanediol and 4,4'-dicarboxyl diphenyl disulfide, stirring in a water bath, and drying to obtain an isocyanate-terminated polyurethane; S6. Add the terminal isocyanate polyurethane obtained in S5 into anhydrous N,N-dimethylacetamide in an amount of 0.4 g / mL, add the straw cellulose obtained in S2, stir in a water bath, and obtain a quick-repair expansion joint polyurethane elastomer composition.
2. The quick-repair expansion joint polyurethane elastomer composition according to claim 1, characterized in that: In S1, the water bath stirring temperature is 60-70°C, the stirring speed is 120-160 rpm, and the stirring time is 15-20 min.
3. The quick-repair expansion joint polyurethane elastomer composition according to claim 2, characterized in that: In S2, the water bath stirring temperature is 70-80°C, the stirring speed is 130-150 rpm, and the stirring time is 25-40 min.
4. The quick-repair expansion joint polyurethane elastomer composition according to claim 3, characterized in that: In S4, the magnetic stirring speed was 250-350 rpm and the stirring time was 50-60 min.
5. The quick-repair expansion joint polyurethane elastomer composition according to claim 4, characterized in that: In S5, the water bath stirring temperature is 76-89°C, the stirring speed is 80-120 rpm, and the stirring time is 6-15 min.
6. The quick-repair expansion joint polyurethane elastomer composition according to claim 5, characterized in that: In S6, the water bath stirring temperature is 72-86°C, the stirring speed is 700-900 rpm, and the stirring time is 80-90 min.
Citation Information
Patent Citations
Polyurethane and preparation method thereof
CN115947921A
Expandable microsphere used in low-temperature environment and preparation method thereof
CN117264130A